A Study of Postoperative Complications Occurring at Home With Pediatric Gastrostomy Feeding Tubes. Issue 1 (28th April 2022) - Aedla, Mihika; Zhou, Anson; Sompel, Kevin; Hu, Katherine; Cheng, Charlotte; Hsu, Jocelyn; Qian, Jason; Zhang, Siya; Ho, Anthony; Slagle, Jacob; Logsdon, Elizabeth A.; Sharma, Karun V.; et al.
Abstract : Objective: Gastrostomy tubes (G-tubes) provide long-term feeding assistance to children with severe feeding dysfunction. Although there are a host of complications that occur at home with current pediatric G-tube feeding, their prevalences and outcomes remain relatively unstudied. This study aims to identify and describe such complications. Methods: A dual-round survey was administered to 98 participants through the Feeding Tube Awareness Foundation, a 501(c)(3) organization that supports parents and caretakers of G-tube-fed children. Information was collected broadly regarding G-tube complications, causes, and attitudes toward such complications. Results: Infection (56%), itching/irritation/redness (52%), and leakage (51%) were the leading G-tube related complications. The average time that G-tubes were replaced was 3.4 ± 1.2 months as compared to the typical recommended period of up to 6 months. Of the caretakers who had not experienced G-tube displacement, 7.9% wanted to see a change in current G-tubes to address the issue, compared with 75% of those who had experienced displacement. This 67.1% differential in caretakers' attitudes toward G-tubes based on their prior experience with a particular complication was the largest gap among all other listed complications. Conclusions: G-tube complications are prevalent and varied. A sizable portion of G-tube users experience complications severe enough to require intervention. Of these, G-tube displacement is particularly critical and frequently precedes other prevalent complications, namely gastric leakage, infection, and tissue granulation.